Approximate solutions to shallow water wave equations by the homotopy perturbation method coupled with Mohand transform - Liu, Yue; Zhang, Yanni; Pang, Jing (Frontiers in Physics, 2023)
In this paper, the Mohand transform based homotopy perturbation method is proposed to solve two dimensional linear and nonlinear shallow water wave equations. This approach has proved suitable for a broad variety of nonlinear differential equations in science and engineering. The variation trend of water surface elevation at different time levels and depths are given by some graphs. Moreover, the obtained solutions are compared with existing results which show the higher efficiency and fewer computations than other approaches studied in the literature.